A new species of the genus Alchemilla (Rosaceae) from Central Russia - Chkalov, Andrey Vyacheslavovich (Phytotaxa, 2015)
A new apomictic species of Alchemilla from several regions of Central Russia is here described as A. tzvelevii. Description and images of the principal morphological features of this species are provided. Alchemilla tzvelevii combines the features of quite distant groups (i.e. A. subsect. Pubescentes and A. subsect. Alchemilla ser. Alchemilla subser. Heptagonae). Its presumed hybridogenous origin is discussed.